Coronavirus disease 2019, COVID-19: Aspects to consider in children - Sánchez-Tauma, Percy J. (2020)
COVID-19 disease is caused by SARS-CoV-2 and currently is considered a pandemic. We present this review article with the aim of describing the characteristics of this disease in children. Some hypotheses have been described that may explain the development of this disease in children, in addition to clinical and laboratory differences compared to adults. No specific treatment has been reported for this population group. Epidemiological studies in children should be carried out according to the context of each region to evaluate the behavior of this disease in this population.